Elucidating Ru Distribution State of Ru‐Promoted Pr2Sn2O7 Pyrochlore and its Effect on the Catalytic Performance for Toluene Deep Oxidation. Issue 8 (8th March 2022) - Liu, Jianjun; Zeng, Lanling; Xu, Xianglan; Xu, Junwei; Fang, Xiuzhong; Bian, Yijun; Wang, Xiang
Abstract: To obtain applicable catalysts for toluene combustion, Ru‐promoted Pr2 Sn2 O7 has been prepared with impregnation (Ru/Pr2 Sn2 O7 ) and hydrothermal method (Ru−Pr2 Sn2 O7 ). For the two Ru/Pr2 Sn2 O7 catalysts, Ru scatters on the surface of Pr2 Sn2 O7 as both metallic Ru and RuO2 . In contrast, for the two Ru−Pr2 Sn2 O7 catalysts, Ru is substituted into Pr2 Sn2 O7 lattice as Ru 4+ . The distribution states of Ru affect significantly the active surface oxygen amount and the toluene adsorption capacity, which are the two major reasons influencing the reactivity. On Ru/Pr2 Sn2 O7, a greater quantity of active oxygen sites can be formed than on Ru−Pr2 Sn2 O7 . Furthermore, the presence of surface Ru 0 facilitates also toluene adsorption. As a consequence, the intrinsic activity of the two Ru/Pr2 Sn2 O7 catalysts are much higher than the two Ru−Pr2 Sn2 O7 catalysts. It is concluded that supporting Ru on Pr2 Sn2 O7 surface is a better way than doping Ru into its lattice to fabricate more active and applicable catalysts. Abstract : Ru‐promoted Pr2 Sn2 O7 has been prepared by both impregnation and hydrothermal method. With impregnation method, both Ru 0 and Ru 4+ are formed on the surface of Pr2 Sn2 O7 (Ru/Pr2 Sn2 O7 ), thus leading to the generation of more abundant chemisorbed active oxygen species (O δ− ) than being incorporated into Pr2 Sn2 O7 lattice matrix as Ru 4+ cations (Ru−Pr2 Sn2 O7 ). Furthermore, the presence of Ru 0 species on catalyst surface is more favourable for toluene molecule adsorption/activation, thereby contributing also to the reactivity. The distribution state of Ru species is the intrinsic reason to affect the catalytic performance.